Effects of Universal Adhesive on Shear Bond Strength of Resin Cement to Zirconia Ceramic with Different Surface Treatments - Zohreh Moradi; Farnoosh Akbari; Sara Valizadeh (International Journal of Dentistry)
Aim. This study aimed to assess shear bond strength (SBS) of resin cement to zirconia ceramic with different surface treatments by using Single Bond Universal. Methods. In this in vitro study, 50 zirconia discs (2 × 6 mm) were divided into 5 groups of (I) sandblasting with silica-coated alumina (CoJet)  + silane + Single Bond 2, (II) sandblasting with CoJet + Single Bond Universal, (III) sandblasting with alumina + Single Bond Universal, (IV) sandblasting with alumina + Z-Prime Plus, and (V) Single Bond Universal with no surface treatment. Resin cement was applied in plastic tubes (3 × 5 mm2), and after 10,000 thermal cycles, the SBS was measured by a universal testing machine. The mode of failure was determined under a stereomicroscope at × 40 magnification. Data were analyzed using one-way ANOVA. Results. The maximum (6.56 ± 4.29 MPa) and minimum (1.94 ± 1.96 MPa) SBS values were noted in groups III and I, respectively. Group III had the highest frequency of mixed failure (60%). Group V had the maximum frequency of adhesive failure (100%). Conclusion. Single Bond Universal + sandblasting with alumina or silica-coated alumina particles is an acceptable method to provide a strong SBS between resin cement and zirconia.